Letter from James Curtis Booth to A. L. Snowden, March 16, 1882 - Booth, James Curtis (1882)
James Curtis Booth (1810-1888) writes to Archibald Loudon Snowden (1835-1912), Superintendent of the United States Mint at Philadelphia from 1879 to 1885, to discuss the technique used in the treatments of sweeps.
Keywords: Booth, James Curtis, 1810-1888; Snowden, Archibald Loudon, 1835-1912; United States Mint; Mint of the United States